OPTICAL AND STRUCTURAL PROPERTIES OF OPTICAL THIN FILMS WITH VARIOUS COLUMNAR MICROSTRUCTURES - Seouk-Hoon Woo; Yong Jun Park; Chang Kwon Hwangbo (ASEAN Journal on Science and Technology for Development, 2007)
In this study, optical and structural properties of the thin films prepared using glancing angle deposition (GLAD) are investigated. Various glancing angles and substrate rotations are employed to control the columnar microstructure of the films. The results show that as the glancing angle increases, the column angle and the porosity of TiO2 films increase and the refractive index decreases, due to shadow effects. The optical anisotropy of tilted and zigzag microstructure TiO2 films have a large anisotropy and reaches a maximum at a glancing angle of 60°, while that of helical microstructure TiO2 film deposited at 60° with substrate rotation shows a very small anisotropy due to the symmetric structure. It is found that the optical anisotropy of TiO2 films deposited by GLAD can be controlled by modification of microstructure.